2016
DOI: 10.1111/zph.12329
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Policy Making by Dairy Producers to Reduce Anti‐Microbial use on Farms

Abstract: Summary Pressures for more responsible use of anti‐microbial (AM) medicines in food animals are likely to increase from policymakers and the food industry, including retailers. To address this challenge, participatory approaches to welfare interventions and disease prevention may also be necessary alongside more conventional regulatory measures. This article describes the process of enabling groups of dairy producers to use a participatory policy making approach to develop an AM stewardship policy. The policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…(2012) as “the systematic use of participatory approaches and methods to improve understanding of diseases and options for animal disease control” [ 50 ]. Participatory methods were used for the development of an antimicrobial stewardship policy in the UK, involving intensive collaboration and dialogue between dairy producers, veterinarians, scientists and industry partners [ 51 ]. This cooperation led to the development of credible and practical recommendations designed to deliver real on-farm changes in the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…(2012) as “the systematic use of participatory approaches and methods to improve understanding of diseases and options for animal disease control” [ 50 ]. Participatory methods were used for the development of an antimicrobial stewardship policy in the UK, involving intensive collaboration and dialogue between dairy producers, veterinarians, scientists and industry partners [ 51 ]. This cooperation led to the development of credible and practical recommendations designed to deliver real on-farm changes in the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Although implementation of such standards may result in improved animal welfare, Fraser (2014) argues that this is best accomplished if it is prompted by farmers rather than by outside stakeholders. For example, in the United Kingdom, 60% of dairy farmers participating in a producer-led program aimed at reducing antimicrobial use on farms reported that they were willing to change practices on their farms (van Dijk et al, 2017). However, another study reported that UK farmers perceived compulsory regulations and government oversight as necessary to enforce the adoption of such agreements (Heffernan Mills et al: LITERATURE REVIEW: MANAGING A DAIRY FARM et al, 2008).…”
Section: Professional Accreditation and Assurance Programsmentioning
confidence: 99%
“…Veterinarians have a prominent role on many farms, providing advice on animal health (Swinkels et al, 2015), treatment protocols (Raymond et al, 2006), animal welfare (Croyle et al, 2019), and antimicrobial stewardship (van Dijk et al, 2017), although individual farmers vary in their intention to contact their veterinarian for advice (e.g., regarding mastitis; Espetvedt et al, 2013). Farmers expect that veterinarians will point out animal welfare issues to which they have become "barn blind" (i.e., "they do not always see something as abnormal because they become accustomed to seeing it every day," Croyle et al, 2019, p. 7390).…”
Section: The Veterinarian As An Advisormentioning
confidence: 99%
“…Population growth and increased urbanization, as well as industrialization (Zhang et al, 2017), have increased the demand for animal protein for human consumption (Boeckel et al, 2015), therefore, the livestock sector in South America has grown at an annual rate of 3.7 %, higher than the average global growth rate of 2.1 %, becoming the region with the largest export of beef and poultry (FAO, 2017), the intensive use of the productive systems of poultry, pigs and dairy cattle at large scale ( Van et al, 2017). These activities are demanding the use of veterinary products for the treatment of diseases, such as lumpy skin (Molla, Frankea, Gari, &de Jong, 2017), protozoan, bacterial, viral, helminthiasis, nutritional andothers (Byaruhanga et al, 2017); antibiotics are also used for the treatment and prevention of diseases in humans (Kim, Lee, & Oh, 2017).…”
Section: Introductionmentioning
confidence: 99%